Religiosity Orientation as A Moderator Between Depression and Suicidal Ideation - Wahyuni, Andi Fitri; Wardana, Rezky Eka; Lathifahani, Rahma (HUMAN: South Asian Journal of Social Studies, 2025)
Abstract. This research explores the connection between depression and suicidal ideation, focusing on whether an individual's religious orientation influences this link. While depression is widely recognized as a major contributor to suicidal thoughts, individual responses to psychological distress vary. One possible moderating factor is how a person engages with and interprets their religious beliefs. Employing a quantitative design with a moderated regression analysis (MRA), the study surveyed 299 university students aged 18–24 from the Greater Jakarta (Jabodetabek) area. Data were collected using validated instruments that assessed depression, suicidal ideation, and religious orientation. The findings indicate that religious orientation plays a moderating role, weakening the association between depression and suicidal ideation. Furthermore, subgroup analysis based on gender demonstrated that the moderating influence of religious orientation is more pronounced in male participants than in females. These insights underscore the potential of religious orientation as a psychological buffer against depression-induced suicidal ideation and highlight its relevance in designing effective prevention and intervention programs. Keywords: depression, suicidal ideation, religiosity, religious orientation, moderation